A rare case of nulligravida with abnormal uterine bleeding, bicornuate uterus, iron-deficiency anaemia, thrombocytopenia and connective-tissue disorder features - Farheen, Khateeb; Jois, Srinivas K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Abnormal uterine bleeding (AUB) frequently causes iron deficiency anaemia; however, coexistence with thrombocytopenia and uterine anomaly is unusual. A 30-year-old nulligravida presented with severe AUB and marfanoid features. Laboratory evaluation showed iron-deficiency anaemia and thrombocytopenia refractory to transfusion. Imaging and intraoperative findings confirmed a bicornuate unicollis uterus with adenomyosis. Total abdominal hysterectomy resulted in normalization of platelet count postoperatively. Severe AUB out of proportion to typical presentation should raise suspicion of Mullerian anomaly. Definitive surgical management can reverse hematologic abnormalities in select cases.